Penerapan Kontrak Jual Beli - Hade Chandra Batubara; Marliyah; Tuti Anggraini (Jurnal EMT KITA, 2023)
Buying and selling is a type of economic activity carried out by sellers and buyers that encourages the exchange of property rights to products or services from the hands of the seller into the hands of the buyer. Buying and selling is a necessity for people to survive. The individual needs of life will the exchange be able to be met through a meeting between merchants and buyers in a place called a market. The development of the market is indistinguishable by the turn of events and changes in the way of life of the individual. The relationship of promise and settlement is that the agreement provides a commitment. Covenants are sources of understanding, regardless of different sources. The agreement is also called understanding, arguing that the two meetings agreed to follow up with something. The understanding brought into the contract world, it must be desired by two people or two meetings to enter into the understanding, while the understanding brought into the world of rules is held by the demonstration is contrary to the wishes of the meeting in question. At the point when two individuals hold an agreement, then, at that moment, they hope that between them there is a legitimate commitment agreement. The purpose of this study is to find out the contents of the Contract of Sale, the object of sale and purchase, and the law of buying and selling. This research uses a type of method The approach method used in this study is a normative approach method, because the legal concept used in this study is a positivist legal concept and views the law of an autonomous institution. The type of research used is a descriptive type of research, because this study aims to provide as much detailed data as possible on the implementation of land sale and purchase agreements. The source of data in this study is secondary data and primary data, where secondary data are complete documents related to the sale and purchase of land, while the primary data is direct information obtained from related parties who can provide information directly the data analysis technique in this study was carried out with documentation study techniques, where data collection was obtained from literature studies and field research.